Eiffel: the (in) disputed beauty of a (in) useful 300-meter tower - Castañeda Silva, César (2023)
The universal exhibitions held since the second half of the 19th century made it possible to show the accelerated advances in science and technology, as well as to witness the tensions in art and architecture trapped in an outdated historicism. The iron and the “structural art” of the engineers will allow debatable ways of facing the architectural fact. A critical moment took place at the Universal Exhibition in Paris in 1889 with the construction of a questionable and useless tower of 300 meters, as a promising building of modernity.